2021
DOI: 10.3389/fpsyg.2021.721806
|View full text |Cite
|
Sign up to set email alerts
|

The Trickle-Down Effect of Territorial Behavior: A Moderated Mediation Model

Abstract: The present research seeks to explore how and when leader territorial behavior trickles down to the follower. Relying on social information processing theory, we hypothesize that territorial behavior has a trickle-down effect from leader to follower, and perceived insider status mediates the relationship between leader territorial behavior and follower territorial behavior. Competition climate is supposed to strengthen the effect of leader territorial behavior on perceived insider status. Two hundred and fifty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…However, Segal et al (2017) claimed that based on a deep understanding of the context, social empathy emphasizes empathy for heterogeneous groups, especially vulnerable or minority groups. Empathy among college students is an altruistic behavior that also promotes other altruistic behaviors ( Li et al, 2015 ; Segal et al, 2017 ). The empathy-altruism hypothesis holds that the core motivation and ultimate purpose of empathy is altruism, i.e., meeting other people’s needs and increasing the spiritual or material well-being of others ( Batson et al, 2015 ).…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…However, Segal et al (2017) claimed that based on a deep understanding of the context, social empathy emphasizes empathy for heterogeneous groups, especially vulnerable or minority groups. Empathy among college students is an altruistic behavior that also promotes other altruistic behaviors ( Li et al, 2015 ; Segal et al, 2017 ). The empathy-altruism hypothesis holds that the core motivation and ultimate purpose of empathy is altruism, i.e., meeting other people’s needs and increasing the spiritual or material well-being of others ( Batson et al, 2015 ).…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…Family supportive supervisor behavior has the ability to convey a benevolent contextual message to employees within the workplace, activating their emotional processing mechanism, fulfilling their emotional needs, and generating positive emotional experiences. Moreover, these experiences possess enduring and pervasive characteristics [56], actively fostering interactions with work or the organization. Consequently, they enhance job satisfaction and organizational commitment, manifest higher levels of dedication and loyalty, and motivate employees to fully tap into their potential, proactively investing greater effort.…”
Section: The Mediating Role Of Affective Commitmentmentioning
confidence: 99%
“…Psychological capital is a positive psychological state encompassing personal resources such as hope, efficacy, resilience, and optimism ( Luthans et al, 2007 ), forming the acronym HERO. Research has consistently shown its significant benefits for work-related outcomes, including performance, productivity ( Peterson et al, 2011 ; Baykal and Zehir, 2018 ), engagement ( Gao et al, 2023 ), innovative behavior ( Karakitapoğlu-Aygün et al, 2020 ; Özsungur, 2020 ; Li et al, 2021 ), and well-being ( Luthans et al, 2013 ; Youssef-Morgan and Luthans, 2015 ). Employees with higher PsyCap levels tend to exhibit be more satisfied, committed, relaxed ( Avey et al, 2010 , 2011b ; Luthans and Youssef-Morgan, 2017 ) and openness to change ( Liu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%